COST AND EFFECTIVENESS OF ATYPICAL-ATYPICAL ANTIPSYCHOTIC COMBINATIONS AND ATYPICAL-TYPICAL ANTIPSYCHOTIC COMBINATIONS IN PATIENTS OF PSYCHOTIC DISORDERS IN INSTALLATION OF EMERGENCY IN GRHASIA MENTAL HOSPITAL, YOGYAKARTA - Arya Dibyo Adisaputra; Endang Darmawan; Arum Siwinarni (Sanata Dharma University, 2021)
Psychotic disorders create a burden on the government, family, and society because of decreasing patient productivity. The use of atypical-atypical and atypical-typical antipsychotic combinations is one of the most commonly used combinations for patients with psychotic disorders. The study was conducted to determine the average total cost and effectiveness of the therapy measured by the difference in PANSS-EC pre-post scores during intensive care. The study was conducted prospectively to analyse the total cost and effectiveness of the therapy using combinations of antipsychotics in psychotic disorders patients. The measured costs include the cost of nursing classes, laboratory, medical treatment, doctor's visit, and antipsychotic. The effectiveness is measured by the difference in PANSS-EC pre-post scores. As many as 32 treated patients with psychotic disorders met the inclusion criteria. The average cost of atypical-typical antipsychotic combination group (Rp1,184,043) was higher than atypical atypical antipsychotic combination group (Rp1,115,829). The effectiveness of the therapy was represented by the value of the difference between the PANSS-EC pre and post scores, which in this research yielded a mean of 7,125 for atypical-atypical antipsychotic combinations and 8,375 for atypical-typical antipsychotic combinations. In conclusion, there is a difference in the total average cost and effectiveness of the therapy. There is a difference between PANSS-EC pre and post scores during the time period from intensive room to quiet room in atypical-typical antipsychotic combinations compared with atypical-atypical antipsychotic combinations.